2011
DOI: 10.1590/s0037-86822011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Espacialização da leptospirose em Aracaju, Estado de Sergipe, no período de 2001 a 2007

Abstract: RESUMOIntrodução: A leptospirose, enfermidade causada por uma espiroqueta patogênica do gênero Leptospira, é uma das zoonoses mais difundidas no mundo, considerada um importante problema de saúde pública. Este trabalho tem como objetivo descrever o padrão espacial da leptospirose na Cidade de Aracaju, no período de 2001 a 2007, buscando identificar as áreas de risco para ocorrência da leptospirose. Métodos: Utilizou-se a razão de kernel, que consiste na criação de uma razão entre duas superfícies, para visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Despite this connection of leptospirosis with floods, there are other factors that may precipitate its emergence, even during dry seasons. A study developed in Aracaju (State of Sergipe, Brazil) on leptospirosis cases during 2001 to 2007 provided a clear illustration of this situation: the authors found no correlation between rainfall and cases of the illness in the city, concluding that occurrence may increase with rainfall, but even in the absence of rain, a certain amount of cases of the disease will occur [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Despite this connection of leptospirosis with floods, there are other factors that may precipitate its emergence, even during dry seasons. A study developed in Aracaju (State of Sergipe, Brazil) on leptospirosis cases during 2001 to 2007 provided a clear illustration of this situation: the authors found no correlation between rainfall and cases of the illness in the city, concluding that occurrence may increase with rainfall, but even in the absence of rain, a certain amount of cases of the disease will occur [41]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies have been conducted in Brazil and other parts of the world, using different geographical scales, producing distinct results. Most of the research has been done in urban areas, mainly slums, followed by rural and wilderness areas [ 2 , 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A aplicação de técnicas de análise espacial no campo da saúde tem grande importância, o Kernel é uma ferramenta útil para obter dados sobre epidemiologia pois representa a relação entre regiões (20) . Trabalhos com técnicas de mapeamento espacial são inestimáveis para a análise de doenças como a tuberculose em tempos históricos (21) .…”
Section: (C) (A) (B)unclassified